State of the Art and Recent Patents on Mg-Based Biodegradable Bone Implants - Neacsu, Patricia; N. Ion, Raluca; Mitran, Valentina; I. Staras, Adela; Cimpean, Anisoara (Recent Patents on Regenerative Medicine, 2014)
Over the past 15 years, the development of magnesium (Mg)-based biodegradable materials has undergone considerable progress and has demonstrated great potential for orthopedic applications. Mg-based biomaterials possess many advantages over newly developed and current applied biomaterials as bone implants, such as favorable in vivo biological properties, mechanical properties and density similar to those of natural bone, and Young’s modulus much lower than Ti-based alloys developed for biomedical applications. However, the main concern with the Mg alloys is related to their rapid corrosion in the physiological environment that can lead to premature failure of the implant due to poor mechanical properties and also to adverse effects caused by the accumulation of metal ions in the surrounding tissues. To adjust the corrosion rate of Mg-based materials so as to match the rates of bone healing, extensive research has been undertaken on modification methods such as alloying and various surface modifications including coating techniques. This article reviews literature and recent patents focusing on strategies used to improve the performance of Mg-based biomaterials.
Keywords: Alloys